Pengaruh Iklim Organisasi, Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Kantor Kementerian Agama Kabupaten Wajo - Agus Purwanto; Suharjum; Fuji Pratiwi; Andi Sumangelipu (Precise Journal of Economic, 2025)
The purpose of this study is to analyze the influence of organizational climate, work motivation, and work environment on employee job satisfaction at the Ministry of Religious Affairs Office in Wajo Regency. This study was conducted at the Ministry of Religious Affairs Office in Wajo Regency. The population was 171 people, and since the population was larger than 100, the sample size was 30% of the total population, which was 51 people. Data collection was carried out using questionnaires, literature, and observation. Data analysis used descriptive statistics and inferential (multiple linear regression). The results of this study indicate that organizational climate, motivation, and work environment, both simultaneously and individually, influence employee job satisfaction at the Ministry of Religious Affairs Office in Wajo Regency. In addition, it was also found that the motivation variable has a dominant influence compared to the other two variables. This study is expected to encourage leaders to increase their attention to employees, especially in terms of organizational climate, motivation, and work environment, because these three factors clearly have a positive influence on employee job satisfaction.